AB1068 Efficacy of anakinra in pseudogout: Report of 3 cases. (23rd January 2014) - Couderc, M.; Mathieu, S.; Glace, B.; Soubrier, M.
Abstract : Background: Anakinra has shown modest efficacy in rheumatoid arthritis and there is proof of principle for its efficacy in gout. Several case reports have suggested it is effective in pseudogout [1-2]. Methods: We report a small study of 3 patients treated with anakinra for pseudogout. Results: Three patients, two men and one woman aged 49, 68 and 68 years, respectively, were treated with subcutaneous anakinra 100mg/day for pseudogout. Diagnosis was based on the association of polyarthralgia and typical X-ray features of pseudogout. In two patients, pseudogout was secondary to haemochromatosis. All three patients had previously received non-steroidal anti-inflammatory drugs and colchicine. Two had been treated unsuccessfully with methotrexate. The first patient did not respond to anakinra (delta DAS +0.3) and treatment was discontinued after 3 months. Anakinra was also stopped in the second patient after 2 months, because of lack of response (delta DAS -0.72) and adverse event. In the last patient, after 3 months of treatment, DAS 28 decreased from 4.83 to 2.31 (delta DAS -2.5) and HAQ from 1.5 to 0.875 and anakinra was continued. Significant side-effects occurred with moderate reaction at the site of injection in two patients and interstitial lung disease in one that could have been due to anakinra. Conclusions: In contrast with previous case-reports, this study showed low efficacy of anakinra in pseudogout. The efficacy of Il-1 blockade treatment in pseudogout needs to be confirmed by randomised controlled studies. References: McGonagle D, Tan AL, Madden J, Emery P, McDermott MF. Successful treatment of resistant pseudogout with anakinra. Arthritis Rheum. 2008;58:631-3. Announ N, Palmer G, Guerne PA, Gabay C. Anakinra is a possible alternative in the treatment and prevention of acute attacks of pseudogout in end-stage renal failure.Joint Bone Spine. 2009;76:424-6. Disclosure of Interest: None Declared